2014
DOI: 10.5812/asjsm.24058
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Scar Detected by Cardiovascular Magnetic Resonance in a Competitive Bodybuilder With Longstanding Abuse of Anabolic Steroids

Abstract: Introduction:The self-administration intake of anabolic-androgenic steroids (AAS) is a widespread practice in competitive bodybuilders. Structural changes within the myocardium following AAS abuse including hypertrophy, restricted diastolic function as well as systolic dysfunction and impaired ventricular inflow have been reported.Case Presentation:We present the case of a 39-year-old bodybuilder with a more than 20-year history of anabolic-androgenic steroids (AAS) abuse presenting with increasing exertional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
0
6
0
5
Order By: Relevance
“…Golestani et al proposed the use of molecular imaging as a method for early detection for CVD in AS users [34]. Baumann et al reported myocardial scaring and cardiomegaly, diagnosed by MRI in a male bodybuilder with 20 years of AS use [35]. Alizade et al found an increase in right ventricular heart strain with the use of a two-dimensional speckle tracking echocardiography [36].…”
Section: Cardiomyopathy and Asmentioning
confidence: 99%
“…Golestani et al proposed the use of molecular imaging as a method for early detection for CVD in AS users [34]. Baumann et al reported myocardial scaring and cardiomegaly, diagnosed by MRI in a male bodybuilder with 20 years of AS use [35]. Alizade et al found an increase in right ventricular heart strain with the use of a two-dimensional speckle tracking echocardiography [36].…”
Section: Cardiomyopathy and Asmentioning
confidence: 99%
“…Additionally, a clinical case report showed that AAS abusers with normal coronary arteries were diagnosed with left ventricular hypertrophy with myocardial scarring. [52] It was also suggested that AAS induces myocardial apoptosis. These studies indicated that AAS had a pro-apoptotic effect on cardiac myocytes.…”
Section: Effects Of Aas On the Cardiovascular Systemmentioning
confidence: 99%
“…Further, the functionality of muscles associated with respiration is vital, and clinical situations such as severe cachexia necessitate therapeutic interventions based on anabolic agents. [36] However, the enormous breadth of yet inevitable undesirable effects of anabolic agents, particularly anabolic-androgenic steroids (AAS), continuously results in reports on risks, [37][38][39][40][41][42][43][44][45][46] documented health damages, [47][48][49][50][51][52][53][54] and fatalities [55] plausibly connected to (long-term) AAS abuse. Despite this steadily growing body of evidence concerning AASrelated adverse health effects, the class of anabolic agents (in particular AAS) has again been most frequently reported with regard to adverse analytical findings in doping control samples.…”
Section: Anabolic-androgenic Steroidsmentioning
confidence: 99%
“…Besides the commonly collected specimens of urine, serum, and whole blood, a growing interest in alternative test matrices such [27][28][29]31,33,35] S1 Anabolic Agents 1 Anabolic androgenic steroids [36][37][38][39][43][44][45][46][47][48][49][50][51][52][53][54][55][56] a. exogenous [63][64][65]67,69,70] 2 Other anabolic agents - [85,86,92,93] - [60,[87][88][89][90][91][92] S2 Peptide hormones, growth factors, related substances and mimetics 1 Erythropoiesis-Stimulating Agents [119] [ 27,33,105,106,112] - [24,27,…”
Section: Introductionmentioning
confidence: 99%